Exploring Motivation, Religiosity, and Perceptions of Career Interest in Sharia Accounting: A Case Study of Accounting Students at STIESA - Jojo Jojo; Hariman Vega; Faza Shidiq; Ana Frasipa (STIESA Press, 2026)
Alim, M. N. (2015). Career interest of accounting students in sharia accounting profession. Procedia - Social and Behavioral Sciences, 211, 984–989. https://doi.org/10.1016/j.sbspro.2015.11.130 Creswell, J. W. (2018). Research design: Qualitative, quantitative, and mixed methods approaches (5th ed.). SAGE Publications. Hamid, S., & Rahman, F. (2017). Religiosity and career choice in Islamic financial institutions. International Journal of Ethics and Systems, 33(2), 165–176. https://doi.org/10.1108/IJOES-05-2017-0076 Ilyas, M. (2020). Akuntansi syariah di Indonesia: Konsep dan implementasi. UII Press. Miles, M. B., Huberman, A. M., & Saldaña, J. (2014). Qualitative data analysis: A methods sourcebook (3rd ed.). SAGE Publications. Moleong, L. J. (2019). Metodologi penelitian kualitatif (Edisi revisi). PT Remaja Rosdakarya. Otoritas Jasa Keuangan. (2023). Statistik perbankan syariah 2023. OJK. Rahmawati, R. (2020). Persepsi mahasiswa akuntansi terhadap profesi akuntansi syariah. Jurnal Akuntansi dan Auditing Indonesia, 24(1), 45–58. https://doi.org/10.20885/jaai.vol24.iss1.art5 Robbins, S. P., & Judge, T. A. (2019). Organizational behavior (18th ed.). Pearson. Ryan, R. M., & Deci, E. L. (2000). Self-determination theory and the facilitation of intrinsic motivation, social development, and well-being. American Psychologist, 55(1), 68–78. https://doi.org/10.1037/0003-066X.55.1.68 Sari, D., & Hidayat, A. (2021). Religiosity, motivation, and students’ career interest in Islamic accounting profession. Journal of Islamic Accounting and Finance Research,